Upah Simpan Barang dalam Skim Ar-Rahnu: Satu Penilaian Semula - Mohamad, Shamsiah; Salleh, Safinar (Jurnal Fiqh, 2008)
The objective of this paper is to evaluate whether the save custody fee imposed by institutions offering Islamic pawn broking facility in Malaysia is in accordance to the Islamic law. For the evaluation purpose, the basis of imposing of the fee i.e. wadi’ah yad damanah is analyzed to ensure that the basis is in line with the percepts of the al-rahn. The study found that the basis did not match the Islamic law. It also found that it is more accurate if the imposing of the fee is based on the expenditure incurred by the murtahin while the goods are in the murtahin`s care due to the fact that the cost is borne by the rahin. The imposing of the fee can also be based on services given by the institutions for their customer